2018
DOI: 10.1136/bmjqs-2018-008364
|View full text |Cite
|
Sign up to set email alerts
|

National hospital mortality surveillance system: a descriptive analysis

Abstract: ObjectiveTo provide a description of the Imperial College Mortality Surveillance System and subsequent investigations by the Care Quality Commission (CQC) in National Health Service (NHS) hospitals receiving mortality alerts.BackgroundThe mortality surveillance system has generated monthly mortality alerts since 2007, on 122 individual diagnosis and surgical procedure groups, using routinely collected hospital administrative data for all English acute NHS hospital trusts. The CQC, the English national regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, some Norwegian hospitals have mortality rates significantly higher than the national average. Although a significant part of the variation observed in hospital mortality can be explained by differences in the case-mix and to random variation, it has been suggested that as much as 30%–60% of this variation can be attributed to differences in the practices and quality of patient care 55. Some hospitals have structures and processes that minimise avoidable patient deaths better than others 56.…”
Section: Discussionmentioning
confidence: 99%
“…However, some Norwegian hospitals have mortality rates significantly higher than the national average. Although a significant part of the variation observed in hospital mortality can be explained by differences in the case-mix and to random variation, it has been suggested that as much as 30%–60% of this variation can be attributed to differences in the practices and quality of patient care 55. Some hospitals have structures and processes that minimise avoidable patient deaths better than others 56.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of incident reporting has been a topic of debate and incident reporting alone is not likely to be sufficient to prevent healthcare associated harm 10. Beyond incident reports, health systems, including the UK National Health Service, have long collected outcome data such as patient mortality and applied these data to detect outlier services with safety concerns 11. A review into state-wide clinical governance in Victoria, triggered by the aforementioned maternity service failure, recommended that multiple and diverse safety performance data, including medicolegal claims, patient complaints and complaints against health practitioners, and outcomes data be shared and analysed jointly to better inform preventative efforts 9.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, regular evaluation of the information provided by the surveillance system is essential. [678]…”
Section: Introductionmentioning
confidence: 99%